Etude de la qualité physicochimique des eaux souterraines de la zone Ouest de Béjaia - HEBIL Yaakob; SAHRAOUI Marwa; ENC/Merzouk Belkacem (My University, 2024)
The main objective of this work is to study the physicochemical quality of groundwater in the western area of Béjaia, belonging to the Oued Soummam sub-watershed. For this purpose, we used measurements and physicochemical analyzes of groundwater in this region, carried out by the Algerian Water Laboratory involving 18 drillings. The use of chemical diagrams (Schöeller-Berkaloff and Piper) and the application of statistical analyzes by different methods, such as, Principal Component Analysis (PCA), Hierarchical Ascending Classification (HAC) and Factor Analysis of Correspondences (FAC) using the XLSTAT software (2014) showed that the calcium and magnesium chloride-sulphate, and the sodium-potassium chloride or sodium sulfate are the most dominant facies due to the geological and hydrogeological nature of the study area
Keywords: Groundwater; Béjaia West; Hydrochemistry; Diagrams; Statistical Analyses